Mutual information analysis reveals coevolving residues in Tat that compensate for two distinct functions in HIV-1 gene expression. - Dey, Siddharth S; Xue, Yuhua; Joachimiak, Marcin P; Friedland, Gregory D; Burnett, John C; Zhou, Qiang; Arkin, Adam P; Schaffer, David V (The Journal of biological chemistry, 2012)
Viral genomes are continually subjected to mutations, and functionally deleterious ones can be rescued by reversion or additional mutations that restore fitness. The error prone nature of HIV-1 replication has resulted in highly diverse viral sequences, and it is not clear how viral proteins such as Tat, which plays a critical role in viral gene expression and replication, retain their complex functions. Although several important amino acid positions in Tat are conserved, we hypothesized that it may also harbor functionally important residues that may not be individually conserved yet appear as correlated pairs, whose analysis could yield new mechanistic insights into Tat function and evolution. To identify such sites, we combined mutual information analysis and experimentation to identify coevolving positions and found that residues 35 and 39 are strongly correlated. Mutation of either residue of this pair into amino acids that appear in numerous viral isolates yields a defective virus; however, simultaneous introduction of both mutations into the heterologous Tat sequence restores gene expression close to wild-type Tat. Furthermore, in contrast to most coevolving protein residues that contribute to the same function, structural modeling and biochemical studies showed that these two residues contribute to two mechanistically distinct steps in gene expression: binding P-TEFb and promoting P-TEFb phosphorylation of the C-terminal domain in RNAPII. Moreover, Tat variants that mimic HIV-1 subtypes B or C at sites 35 and 39 have evolved orthogonal strengths of P-TEFb binding versus RNAPII phosphorylation, suggesting that subtypes have evolved alternate transcriptional strategies to achieve similar gene expression levels.
Keywords: Evolution, Molecular; Gene Expression Regulation, Viral; Genome, Viral; HEK293 Cells; HeLa Cells; HIV-1; Humans; Mutation; Phosphorylation; Positive Transcriptional Elongation Factor B; Protein Structure, Tertiary; RNA Polymerase II; Species Specificity; tat Gene Products, Human Immunodeficiency Virus; Virus Replication